Optimasi Produksi Poli-β-Hidroksibutirat (PHB) oleh Bacillus sp. PSA10 - Nur Arfa Yanti; Sebastian Margino; Langkah Sembiring (Universitas Atma Jaya Yogyakarta, 2010)
A new strain characterized as Bacillus sp. PSA10 was found to produce poly-β-hydroxybutyrate (PHB) at concentration of 52.28% (g PHB/g dry cell weight) in shaken flask culture, using sago starch as a carbon source. This research is aimed to determine the optimum culture condition of PHB production Bacillus sp. PSA10 at laboratory scale. Optimization of PHB production was conducted in this research, in terms of inoculum concentration, concentration of the major components in minimal medium, environmental condition and incubation time. The result showed that optimum conditions for the production of PHB by Bacillus sp. PSA10 were achieved at minimal medium (Ramsay medium) with 5% (v/v) inoculum concentration, 2% (w/v) sago starch, 1.0 g/l (NH4)2SO4, 6.7 g/l Na2HPO4.7H2O, and 0 g/l KCl. The optimum environmental conditions were achieved with initial pH 7, temperature 37oC, agitation speed at 150 rotary per minute (rpm) and the best of incubation time was 48 hour. Under this optimum condition, the maximum PHB production by Bacillus sp. PSA10 increased from 52.28% to 71.35% (g PHB/g dry cell weight) at 48 hour cultivation. Therefore, Bacillus sp. PSA10 is potential to apply for PHB production from sago starch at industrial scale.